Cardioprotective effects of preconditioning exercise in the female tumor bearing mouse - Parry, Traci L.; Tichy, Louisa; Brantley, Jason T. (Frontiers in Cell and Developmental Biology, 2022)
Cancer cachexia, a metabolic wasting syndrome, affects up to 80% of cancer patients and leads to the death in up to 20% of cancer patients. While research is growing in the field, there are still no clear diagnostic criteria and cancer cachexia remains an untreated condition. Aerobic exercise has been shown to positively impact cachexia by slowing its development and attenuating muscle loss. The most effective timing, duration, and intensity of exercise as a preventative and protective measure against cancer cachexia remains questionable. Therefore, the purpose of this study was to examine the effects of preconditioning exercise as a protective measure for tumor-mediated muscle wasting. Female LC3 Tg+ and WT mice were randomly separated into four groups, sedentary non-tumor bearing (SED+NT), sedentary tumor bearing (SED+T), treadmill exercise non-tumor bearing (TM+NT), and treadmill exercise tumor bearing (TM+T). Mice underwent an 8-week treadmill exercise training protocol (TM) or remained sedentary (SED). Next, mice were implanted with tumor cells (T group; 5x105 LLC cells in flank) or remained non-tumor (NT) for 4 weeks. Tumor bearing resulted in a significant decline in cardiac function. SED+T showed a significant decrease in fractional shortening (P < 0.05) when compared to the other groups. This coincided with an increase in beclin-1 expression in SED+T mice. Interestingly, preconditioning exercise (exercise prior to tumor bearing) appeared to preserve cardiac function (TM+T not significantly different than SED+NT). Exercise-mediated cardioprotection also coincided with abolished beclin-1 signaling since this was not significantly elevated in TM+T mice. Additionally, TM resulted in a 22-fold decrease in estimated tumor volume (P < 0.05) and a 45% decrease in tumor mass (P < 0.05) compared to SED tumors. The data indicate potential cardioprotective effects of preconditioning exercise on preserving cardiac structure and function, as well as regulating autophagic pathways (beclin-1) during tumor bearing. Preconditioning exercise may be an effective and accessible treatment intervention for early-stage cancer survivors. This data is crucial in identifying the significance of exercise and the timing of exercise as a protective measure against the detrimental effects of cancer cachexia.